Resistance training is associated with higher lumbar spine and hip bone mineral density in competitive male cyclists - Mathis, S. L.; Caputo, J. L. (The Journal of Strength and Conditioning Research, 2018)
In contrast to other athletic activities, competitive cycling is associated with low areal bone mineral density (BMD). This investigation evaluated training and dietary factors associated with BMD in a sample of competitive male cyclists. Lumbar spine, total hip, femoral neck, and femoral trochanter BMD were measured with dual X-ray absorptiometry in 40 cyclists at the start of a cycling season. Participants reported weekly hours of cycling and weight training, years of competitive cycling experience, and completed a 1-day dietary recall to allow estimation of dietary calcium intake. Multivariable linear regression analyses revealed that weight training was associated with higher BMD of the lumbar spine (ß = 0.001, t = 2.88, p = 0.01), hip (ß = 0.002, t = 4.95, p < 0.001), femoral neck (ß = 0.002, t = 5.31, p < 0.001), and femoral trochanter (ß = 0.002, t = 4.31, p < 0.001). No other factor was a predictor of preseason BMD in this sample. These data emphasize the need for competitive male cyclists to participate in weight training to maintain or increase bone mass of the lumbar spine and hip.